O processo de coaching nas organizações empresariais - Garcia, Ana Lúcia (2012)
This dissertation has as its theme the coaching process conducted business with an emphasis on leadership of a private company. The role of researcher on this study was a psychologist/external Organizational Consultant contracted to a wide Project of Professionalization. The thesis comprises two sections: section I, we present the business coaching under the gaze of systemic approaches-complex and the ACP (approach centered on the person). The proposal in this section is to deepen theoretically as the interaction of these two embasamentos theorists associated with the process of business coaching. In section II, whittling away the main movements, steps and business coaching process results from an empirical research. In which this was aimed at General, examine the operational and behavioral changes produced by the process of coaching in an organizational context. We use a qualitative approach which examined the documents produced in the process of coaching in the year 2009. The survey results indicate that the process of coaching as an organizational development strategy coupled with broad was effective in developing operational and behavioral skills of the leaders involved. Such changes had an impact on the organizational environment, but also, in the context of professional and personal lives of coachees. Attitudes from facilitating person-centric approach and printed in the practices of coaches allowed growth to all involved. How restrictive the empirical factor this part, we have the research training of evaluators of coachees, where could have occurred more frequently.